Impact of vitamin D on human embryo implantation: a prospective cohort study in women undergoing fresh embryo transfer - Cai, Sufen; Li, Jian; Zeng, Suimin; Hu, Liang; Peng, Yangqin; Tang, Sha; Zeng, Shufei; Chu, Chang; Gong, Fei; Lin, Ge; Hocher, Berthold (Fertility and sterility, 2021)
Objective - To measure free and total 25-hydroxyvitamin D [25(OH)D] immediately before embryo transfer and analyze its association with early pregnancy outcome parameters such as biochemical pregnancy, implantation rate, and clinical pregnancy rates in women undergoing fresh embryo transfer after their first ovarian hyperstimulation. - Design - Prospective cohort study. - Setting - Academically affiliated private fertility center. - Patient(s) - A total of 2,569 women undergoing fresh embryo transfer after ovarian hyperstimulation. - Interventions(s) - None. - Main Outcome Measure(s) - The study end points were biochemical pregnancy rate, implantation rate, clinical pregnancy rate, ectopic pregnancy rate, early miscarriages, and ongoing pregnancy rate. Free and total 25(OH)D concentrations were measured 1 day before embryo transfer. - Result(s) - Total 25(OH)D correlated with free 25(OH)D. Total and free 25(OH)D serum concentrations were similar in those patients reaching and not reaching the study outcomes (biochemical pregnancy rate, implantation rate, clinical pregnancy rate, ectopic pregnancy rate, early miscarriages, and ongoing pregnancy rate). There was likewise no statistical difference when analyzing the frequency of all study outcomes in quintiles of either total or free 25(OH)D. In addition, the study population was divided into three groups according to the total vitamin D status based on clinical practice guideline. All outcomes were similar in women with adequate, insufficient, and deficient total 25(OH)D. Multiple linear regression analysis considering confounding likewise indicated no association of free or total vitamin D with any of the study outcomes. - Conclusion(s) - Neither free nor total 25(OH)D concentration at embryo transfer was associated with successful embryo implantation in women undergoing fresh transfer after ovarian hyperstimulation. - Impacto de la vitamina D en la implantación embrionaria humana - un estudio prospectivo de cohortes en mujeres sometidas a transferencia embrionaria en fresco. - Objetivo - Medir la 25-hidroxivitamina [25(OH)D] libre y total justo antes de la transferencia embrionaria y analizar su asociación con resultados gestacionales como la gestación bioquímica, tasas de implantación y de gestación clínica en mujeres con transferencia en fresco después de su primera estimulación ovárica. - Diseño - Estudio prospectivo de cohortes. - Lugar - Centro privado de reproducción asociado a centro académico. - Paciente(s) - Un total de 2569 mujeres sometidas a transferencia embrionaria en fresco después de estimulación ovárica. - Intervención(es) - Ninguna. - Medida(s) principal(es) de resultado - Los objetivos finales del estudio fueron las tasas de gestación bioquímica, de implantación, de gestación clínica, de gestación ectópica, de abortos tempranos y gestación evolutiva. Las concentraciones de 25(OH)D libre y total fueron medidas un día antes de la transferencia embrionaria. - Resultado(s) - La 25(OH)D total correlacionó con la libre. Las concentraciones séricas total y libre de 25(OH)D fueron similares entre quienes alcanzaron o no los resultados del estudio (tasas de gestación bioquímica, implantación, gestación clínica, gestación ectópica, abortos tempranos y gestación evolutiva). Hubo igualmente ausencia de diferencias significativas cuando se analizó la frecuencia de todos los resultados del estudio en quintiles para 25(OH)D total o libre. Adicionalmente, la población estudiada fue dividida en tres grupos según el estado de vitamina D total basado en la guía de prácticas clínicas. Todos los resultados fueron similares en mujeres con concentraciones adecuada, insuficientes o deficientes de 25(OH)D total. El análisis de regresión lineal múltiple considerando factores de confusión, tampoco indicó asociación entre vitamina D total o libre con ninguno de los resultados del estudio. - Conclusión(es) - Ni la concentración de 25(OH)D libre ni total al momento de la transferencia embrionaria estuvo asociada con la implantación embrionaria exitosa en mujeres sometidas a transferencia embrionaria en fresco después de la estimulación ovárica. - Palabras clave - 25-Hidroxivitamina D, 25-Hidroxivitamina D libre, 25-Hidroxivitamina D total, implantación embrionaria, transferencia embrionaria.
Gesehen am 10.09.2021